Time Course of Root Axis Elongation and Lateral Root Formation in Perennial Ryegrass (Lolium perenne L.) - Arif Hasan Khan Robin; Louis John Irving; Jim Crush; Hans Schnyder; Fernando Alfredo Lattanzi; Cory Matthew (Plants, 2021)
Grasses have a segmental morphology. Compared to leaf development, data on root development at the phytomer level are scarce. Leaf appearance interval was recorded over time to allow inference about the age of segmental sites that later form roots. Hydroponically grown Lolium perenne cv. Aberdart tillers were studied in both spring and autumn in increasing and decreasing day length conditions, respectively, and dissected to define the development status of roots of known age on successive phytomers basipetally on the tiller axis. Over a 90-day observation period spring and autumn tillers produced 10.4 and 18.1 root bearing phytomers (Pr), respectively. Four stages of root development were identified: (0) main axis elongation (~0–10 days), (1) primary branching (~10–18 days), (2) secondary branching (~18–25 days), and (3) tertiary and quaternary branching without further increase in root dry weight. The individual spring roots achieved significantly greater dry weight (35%) than autumn roots, and a mechanism for seasonal shift in substrate supply to roots is proposed. Our data define a root turnover pattern likely also occurring in field swards and provide insight for modelling the turnover of grass root systems for developing nutrient efficient or stress tolerant ryegrass swards.